Therapeutic Potential of Resveratrol in COVID-19-Associated Hemostatic Disorders - Giordo, Roberta (Molecules, 2021)
Coagulation disorders, endotheliopathy and inflammation are the most common hallmarks in SARS-CoV-2 infection, largely determining COVID-19’s outcome and severity. Dysfunctions of endothelial cells and platelets are tightly linked in contributing to the systemic inflammatory response that appears to be both a cause and a consequence of COVID-19-associated coagulation disorders and thrombotic events. Indeed, elevated levels of circulating inflammatory cytokines are often associated with abnormal coagulation parameters in COVID-19 patients. Although treatments with low molecular weight heparin (LMWH) have shown beneficial effects in decreasing patient mortality with severe COVID-19, additional therapeutic strategies are urgently needed. Utilizing the anti-inflammatory and anti-thrombotic properties of natural compounds may provide alternative therapeutic approaches to prevent or reduce the risk factors associated with pre-existing conditions and comorbidities that can worsen COVID-19 patients’ outcomes. In this regard, resveratrol, a natural compound found in several plants and fruits such as grapes, blueberries and cranberries, may represent a promising coadjuvant for the prevention and treatment of COVID-19. By virtue of its anti-thrombotic and anti-inflammatory properties, resveratrol would be expected to lower COVID-19-associated mortality, which is well known to be increased by thrombosis and inflammation. This review analyzes and discusses resveratrol’s ability to modulate vascular hemostasis at different levels targeting both primary hemostasis (interfering with platelet activation and aggregation) and secondary hemostasis (modulating factors involved in coagulation cascade).